Innovation In Processing Of Areca Peel Waste Into Organic Polybags As Nursery Media - Adinda Salwa Rahmasari; Azzahra Oftan; Yolanda Putri; Ray Ferdinand; Zaskhia Melani; Hariance, Rika (Jurusan Budidaya Perkebunan, 2023)
Polybags are planting media that are often used as nursery media. However, the use of polybags can cause the environment to become polluted due to the use of plastic, which is difficult to decompose by soil microbes, and also can destroy planting media and caused root damage in planting process to the field. One way to overcome these problems is to use organic-based nursery containers that are environmentally friendly. Poliarec (Polybag Organic of Areca catechu) is an organic polybag derived from areca peel waste. This product was made in 3 stages, first stages by making of polybags using 250 gr of areca peel waste to produce one unit of polybag measuring 10x10 cm. The second stage was carried out weight and density tests, and the third stage was carried out functional tests by conducting planting experiments on horticultural seeds. Poliarec can be planted directly on the ground because it is easily decomposed by microbes so that it can simultaneously become fertilizer and is able to maintain soil moisture. The density test showed, Poliarec has a low density category type based on SNI standards. It can function well as a seedling media after a functional test on chili seeds for 4 weeks. From this functional test, it was also found that Poliarec can save water usage because watering can be done once every three days. The direct benefits of this creative and innovative work are in addition to support sustainable agriculture by reducing the use of plastic polybags, and also will increasing the economic value of areca peel waste.